Analysis of Empowerment of PT Sumber Alfaria Trijaya (Alfamart) Bandung 2 (Cimahi) UMKM Empowerment - Iman Sulaeman; Daffa Maulana Safa (MANAGER: Journal of Management and Administration Science, 2023)
This study aims to determine the pattern of partnership between Alfamart and its UMKM partners, explain the strengths and weaknesses as well as the opportunities and threats that the company has in carrying out UMKM empowerment. The research method used is qualitative in the SWOT matrix. This research was conducted at the Bandung 2 branch of Alfamart, Cimahi. The results of this study are: the UMKM empowerment process carried out by Alfamart in the form of, providing good prices, product information that was selling at the time, evaluation through base on data, providing stall surgery facilities for active or loyal members in purchasing and providing various kinds of training to fostered SMEs. The result of the calculation of the SWOT analysis on empowering UMKM that is obtained is the difference between strengths and weaknesses of 9 and the difference between opportunities and threats is 1. So, the results of the SWOT analysis of UMKM empowerment carried out by Alfamart are in quadrant I (positive-positive ). So that Alfamart is considered quite capable of using the strengths and weaknesses within the company and taking advantage of opportunities and minimizing existing threats.